Mind Over Plate: The Hypnotic Influence on Dietary Intake among Adults with Overweight and Obesity in Terengganu, Malaysia - Roslim, Nurul Afiedia; Ahmad, Aryati; Mansor, Mardiana; Thwe Aung, Myat Moe; Hamzah, Farrahdilla; Lua, Pei Lin (Jurnal Gizi dan Pangan, 2025)
This study aimed to evaluate the effectiveness of hypnotherapy in improving dietary intake and weight status of young adults with high Body Mass Index (BMI) in a public university in Terengganu, Malaysia. This pre-and post-intervention randomly assigned 107 participants with BMI≥25 kg/m2 to either the Intervention Group (IG=53) or the Control Group (CG=54), for 12 weeks. All participants received health education (diet + exercise + behavioral recommendations) and completed food records, while those in IG had additional three hypnotherapy sessions once a month. Descriptive statistics and repeated measure Analysis of Covariance (ANCOVA) were utilized (SPSS 23.0). A total of 104 participants completed the trial (female=82.2%; student=71.0%; BMI=31.3±5.0 kg/m2). Results demonstrated significant decrements in weight (Mean Difference (MD)=-1.4 kg; p=0.021), total energy (MD=-269 kcal; p=0.033), carbohydrate (MD=-1.0% EI; p=0.019) and total fats (MD=-1.8% EI; p=0.002) intakes in IG after controlling for age, gender and baseline variables on repeated measurements. Hypnotherapy had a positive impact on energy intake, indicating its effectiveness in tackling eating habits. These findings are promising and could serve as a basis for future studies in hypnotherapy for weight loss.